INTELIGENTNÉ DOPRAVNÉ SYSTÉMY A ELEKTRONICKÉ OBCHODOVANIE V NÁKLADNEJ DOPRAVE (Perner's Contacts, 2007)
The article describes use of intelligent transport systems, electronic business tools and systems in goods transport.
Keywords: Intelligent transport systems; Logistics; Electronic business; Transport